PKM PENGEMBANGAN MANAJEMEN TEKNOLOGI PENGELOLAAN BAMBU SEBAGAISUMBERDAYAALAMLOKALDANMEUBELKURSIDIKABUPATEN PINRANG PROVINSI SULAWESISELATAN - Fatriady MR; Rani Bastari Alkam (Forum Layanan IPTEKS Bagi Masyarakat (FLipMAS) Wilayah Bali, 2019)
The target of the Community Partnership (PKM) program is an economically productive community group (small business). The aim of the program is to develop economically independent communities. The business partners in this program are the